New finds of charophytes in Iceland with an update on the distribution of the charophyte flora. (26th May 2019) - Hrafnsdottir, Thora; Ingimarsson, Finnur; Ingvason, Haraldur R.; Stefánsson, Stefán Már; Þorvaldsdóttir, Eva G.; Malmquist, Hilmar J.; Langangen, Anders
Abstract : Charophyte species new to the flora of Iceland are reported and an update on the distribution of the previously known species is given. Four species are new to Iceland; Chara aspera Willdenow, Chara contraria Braun ex Kützing, Tolypella canadensis Sawa and Tolypella glomerata (Desvaux) Leonhardi, while four species were previously known: Chara globularis Thuiller, Chara virgata Kützing, Nitella flexilis (L.) Agardh and Nitella opaca (Agardh ex Bruzelius) Agardh. The finding of the species new to Iceland add to the hitherto known worldwide distribution of those species, including a significant extension to the north.